Geochemical character of amphibolites from Tisza Unit on the basis of incompatible trace elements - M. Tóth Tivadar (Acta mineralogica-petrographica, 1994)
Pre-metamorphic origin of amphibolites and amphibolic gneisses from K6ros Complex (Eastern Tisza Unit) has been an unsolvable problem for a long time. Last year the trace element (Zr, Y, Nb, Ti, P) composition of almost 100 amphibolite samples were measured and this data base may be useful for determining pre-metamorphic rock types and petrochemical character of amphibolites. Present examinations show that - opposite to the previous results - there were no alkaline magmatites in the area, but the rocks of both tholeiitic and calk-alkaline series were formed. The data also suggest that the original igneous rocks of amphibolic gneisses developed in an island arc, while the amphibolites' either in a fore-arc or in a back-arc basin.